2015
DOI: 10.1144/sp416.14
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of particulate matter in attic and settled dusts collected from two buildings in Budapest, Hungary

Abstract: We have investigated two buildings covered with Zsolnay glazed architectural ceramics in Budapest (Hungary), one located in the densely built-up area of the city centre with a high traffic rate and one in a city quarter with moderate traffic and more open space. A black crust layer, containing a large amount of artificial particulate matter with different size and chemical composition, was observed on the ceramic material of both buildings, whereas weathered glaze was detected only on the ceramics of the build… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
1
0
1
Order By: Relevance
“…Összefüggést mutattak ki a gipszesedés és a felszínen megkötött, szállóporban megjelenő, mesterséges (antropogén eredetű) szferulák jelenléte között. Ezen részecskék összetételük, katalizáló fémtartalmuk és szivacsos felületük révén elősegítik a szulfátosodás folyamatát (Hutchinson et al 1992, Baricza et al 2016b.…”
Section: Fekete Lerakódás -A Külső Környezet Hatása a Pirogránitraunclassified
“…Összefüggést mutattak ki a gipszesedés és a felszínen megkötött, szállóporban megjelenő, mesterséges (antropogén eredetű) szferulák jelenléte között. Ezen részecskék összetételük, katalizáló fémtartalmuk és szivacsos felületük révén elősegítik a szulfátosodás folyamatát (Hutchinson et al 1992, Baricza et al 2016b.…”
Section: Fekete Lerakódás -A Külső Környezet Hatása a Pirogránitraunclassified
“…Baricza et al (2015) focused on the very specific problem of the decay of glazed decorative and structural ceramic elements used on historical buildings in Budapest (Hungary). By detailed analytical study, they found three distinct types of pollutants (dust particles), differing in composition and size.…”
Section: Prevention and Mitigation Of Decaymentioning
confidence: 99%